2011
DOI: 10.1128/jvi.02566-10
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Geminivirus Replication Protein and the SUMO-Conjugating Enzyme Is Required for Viral Infection

Abstract: Geminiviruses are small DNA viruses that replicate in nuclei of infected plant cells by using plant DNA polymerases. These viruses encode a protein designated AL1, Rep, or AC1 that is essential for viral replication. AL1 is an oligomeric protein that binds to double-stranded DNA, catalyzes the cleavage and ligation of single-stranded DNA, and induces the accumulation of host replication machinery. It also interacts with several host proteins, including the cell cycle regulator retinoblastoma-related protein (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 91 publications
4
67
2
Order By: Relevance
“…To detect the SUMOylated form of NIb, an NIb-His fusion protein was transiently expressed in plants. However, possibly due to the reversible nature of the SUMOylation process or to only a very small amount of viral protein being SUMOylated, as suggested previously (20), the SUMOylated form of NIb was not detected by immunoblotting (data not shown). An E. coli strain system that was reconstituted with the SUMO conjugation pathway (30) was employed for SUMOylation assay.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…To detect the SUMOylated form of NIb, an NIb-His fusion protein was transiently expressed in plants. However, possibly due to the reversible nature of the SUMOylation process or to only a very small amount of viral protein being SUMOylated, as suggested previously (20), the SUMOylated form of NIb was not detected by immunoblotting (data not shown). An E. coli strain system that was reconstituted with the SUMO conjugation pathway (30) was employed for SUMOylation assay.…”
Section: Resultsmentioning
confidence: 58%
“…3C). This phenomenon was frequently ob- served for proteins containing multiple SUMOylation sites, possibly owing to the fact that each SUMOylation site may be conjugated by a different number of SUMO molecules (20). Indeed, analysis of the entire NIb by use of the SUMOylation prediction program revealed additional potential SUMOylation motifs (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar connections have been observed in animals, including roles in anaerobic tolerance (34,35) and genotoxic stress (36). Numerous plant and animal pathogens also have been shown to synthesize factors that promote infection by interfering with host SUMOylation (37,38).…”
mentioning
confidence: 57%
“…Further analysis revealed that the interaction between Rep and SUMO E1 is required for viral DNA replication and viral infectivity. Overexpression of Rep did not alter the general SUMOylation pattern of plant proteins, but as few additional conjugated proteins were detected, it was proposed that modulation of SUMOylation may be limited to specific host proteins, which remain to be defined (Sánchez-Durán et al, 2011).…”
Section: Sumoylation Of Viral Replication Proteinsmentioning
confidence: 99%